RETRACTED: Russian Volga federal district regions’ digitalisation as a factor of their sustainable development - Eflova Maria; Glebova Irina; Zakirov Ayaz; Vavilova Tatyana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001